What Shapes Leadership? A Systematic Literature Review Of Communication, Interaction, And Social Construction Perspectives - Emanuel Hindro Cahyono; Lucia Rini Sugiarti; Fendy Suhariadi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This systematic literature review examines what shapes leadership through the lenses of communication, interaction, and social construction. Drawing on interdisciplinary scholarship from leadership studies and communication theory, the review synthesizes research that conceptualizes leadership not as an individual trait or positional authority, but as a dynamic, relational, and communicative process. Using a systematic search and screening procedure, the study analyzes key theoretical and empirical contributions that emphasize meaning-making, interactional practices, discourse, and socially constructed realities in leadership processes. The findings indicate that leadership emerges through ongoing communication, including sensemaking, framing, dialogue, and negotiated interactions among leaders, followers, and broader stakeholders. Rather than residing solely in individuals, leadership is shown to be co-constructed within social contexts shaped by language, power relations, cultural norms, and organizational settings. This review highlights a shift from leader-centric models toward relational, distributed, and process-oriented perspectives, underscoring communication as constitutive of leadership itself. The study contributes to leadership scholarship by integrating communication and social construction perspectives into a coherent framework, offering implications for future research and leadership development practices that prioritize interaction, reflexivity, and collective meaning-making in complex organizational and social environments.